Rice yield in Costa Rican Central Pacific did not improve with a urease inhibitor - Pérez-Castillo, Ana Gabriela; Giraldo-Sanclemente, Weynner; Monge-Muñoz, Mayela; Chinchilla-Soto, Cristina; Alpízar-Marín, Melvin; Zaman, Mohammad (Frontiers in Agronomy, 2024)
Urea is widely used as nitrogen (N) source for rice fertilization in Costa Rica, despite its low efficiency linked to ammonia losses. To assess urea management alternatives, two field experiments were conducted in the Central Pacific region of Costa Rica to study the effect of N-(n-butyl) thiophosphoric triamide (NBPT) on rice yield and N use efficiency (NUE). In Experiment 1 (Exp1) three tillage treatments (commercial-CT-, reduced-RT-, and reduced tillage with previous subsoiler-RTS-) were evaluated with three N managements: control (without N), urea at 124 kg N ha-1 with and without NBPT. In Experiment 2 (Exp2), a 100 kg N ha-1 dose (with and without NPBT) was evaluated along with a control (without N). NUE was estimated using 15N urea isotopic labeling technique for both trials. In Exp1, a significant difference of 4.8% in NUE for grain was observed among urea with and without NBPT, but no tillage effect was observed. No statistically significant differences were observed in yield among the fertilization treatments (Exp1: 3.56 ± 0.98 t ha-1 for urea and 3.85 ± 0.85 t ha-1 for urea with NBPT; Exp2: 3.38 ± 0.39 t ha-1 for urea and 3.40 ± 0.58 t ha-1 for urea with NBPT) or due to different tillage practices (CT: 3.33 ± 0.79 t ha-1 , RT: 3.56 ± 0.74 t ha-1 , and RTS: 4.23 ± 0.98 t ha-1). Although the NBPT is a viable option to reduce ammonia losses, its adoption in tropical conditions might be restricted by the small impact on yield.